2018
DOI: 10.1177/2158244018820376
|View full text |Cite
|
Sign up to set email alerts
|

“Loving Nursing” and “Taking Responsibility”: Strategies for Transitioning to Practice in Lebanon

Abstract: Transitioning to practice is challenging for baccalaureate nursing students. In baccalaureate nursing programs, the process typically begins in the junior year. A Successful transition depends on how well students apply their developing knowledge during clinical placements. A cross-sectional, multisite, qualitative study was conducted at four universities in Greater Beirut, Lebanon. In total, 35 junior baccalaureate students participated in audio-recorded focus group discussions. Thematic analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While it is expected that all parties involved in teaching and learning accept and assume their role, the conceptions in this study showed that the parties are at different levels of understanding their roles. Clinton et al, [ 80 ] supports this finding who reported that students gradually assume responsibility of their learning as their understanding develops. Similar scenarios are displayed in nurses who struggle to balance their patient care responsibility and students teaching [ 81 ].…”
Section: Discussionmentioning
confidence: 69%
“…While it is expected that all parties involved in teaching and learning accept and assume their role, the conceptions in this study showed that the parties are at different levels of understanding their roles. Clinton et al, [ 80 ] supports this finding who reported that students gradually assume responsibility of their learning as their understanding develops. Similar scenarios are displayed in nurses who struggle to balance their patient care responsibility and students teaching [ 81 ].…”
Section: Discussionmentioning
confidence: 69%
“…We make no claim to objectivity because this article is not concerned with defending the research findings we have reported elsewhere. (Clinton, Ezzeddine, et al, 2018; Clinton, Madi, et al, 2018; Madi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sophomore and senior baccalaureate nursing students attended program‐level focus groups. The focal question the participants discussed was 'What challenges are you facing as you transition to practice?’ Interested readers are referred to our previous publications for more details (Clinton, Ezzeddine, Doumit, Rizk, & Madi 2018; Clinton, Madi, Doumit, Ezzeddine, & Rizk, 2018; Madi, Clinton, Doumit, Ezzeddine, & Rizk, 2018).…”
Section: Introductionmentioning
confidence: 99%